Studi Prototipe Alat Pemintal Pelepah Pisang Bagi Kelompok Pengrajin Gedebog Pisang di Desa Kedungkeris - Iva Mindhayani; Masrul Indrayana; Niken Permatasari (Universitas Widya Mataram, 2024)
Banana trees are commonly found in the village of Kedungkeris, Nglipar District,Gunung Kidul Regency. The abundance of banana trees has not yet been utilized to itsfullest potential. After being cut down, the banana tree trunks are simply left to rot, eventhough they have economic value. The objectives of this activity are: 1) To transferknowledge and technology (IPTEKS) as a tangible manifestation of the Tri Dharma ofHigher Education carried out by lecturers from Universitas Widya Mataram, and 2) Tocreate a banana pseudostem spinner and test the tool. The methods used are: 1)Preparation and planning, 2) Designing, 3) Fabricating the tool, 4) Testing the tool, and5) Evaluating the results of the tool testing. The results of this activity indicate thatimprovements are needed in the braking system, the technique for connecting bananapseudostems, and the dryness level of the banana pseudostems.